Transformation of Professionalism in the World of Education: Effective Management Strategies for Developing the Behavior and Competence of Educational and Teaching Personnel - I Made Ardika Yasa; Anak Agung Gde Agung; Ni Luh Gede Erni Sulindawati (Jurnal Syntax Admiration, 2023)
This article discusses the importance of professional development and behavior management for educational staff and teachers in the field of education. A descriptive qualitative method is used to explore effective strategies in professional development and behavior. The analysis involves identifying individual needs and potential to formulate suitable development plans. Furthermore, integrated and sustainable training and development programs are outlined, aiming to enhance the quality of teaching and educational services. Active engagement of learners is emphasized, with a focus on ethics, attitudes, and effective communication in the educational environment. Collaborative approaches and team-based learning promote synergy among educational staff and teachers to achieve better educational goals. Continuous evaluation and feedback are crucial in enhancing program effectiveness. This article provides guidance for educational institutions and policy-makers in designing impactful professional development and behavior programs to improve the quality of education and address complex future demands.